Strategic innovation and its impact on manufacturing SME performance in Yemen - AlQershi, Nagwan; Abas, Zakaria; Mohd Mokhtar, Sany Sanuri (2018)
It is widely believed in the literature and among practitioners that Small and Medium enterprises are instrumental to the economic development of countries all over the world.However, the contribution of SMEs can only be possible through performance.This study is a conceptual discussion of manufacturing SME performance in Yemen and the effect of strategic innovation.The performance of manufacturing SMEs in Yemen is considered to be very low, and the country is ranked as one the lowest in terms of innovation by the Global Innovation Index.The study discusses strategic innovation and presents a framework for understanding the concept through 15 different ways.It concludes by recommending some policies through which the government of Yemen can assist manufacturing SMEs.Specifically, the study recommends that the government should provide training subsidies to manufacturing SMEs in the country because innovation can only take place when human resources are adequately trained.